2007
DOI: 10.1080/10715760701361531
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypoxia promotes an aggressive phenotype in rat prostate cancer cells

Abstract: In general, tumors cells that are resistant to apoptosis and increase angiogenesis are a result of the hypoxic responses contributing to the malignant phenotype. In this study, we developed a chronic hypoxic cell model (HMLL), by incubating the prostate cancer MatLyLu cells in a hypoxic chamber (1% O(2)) over 3 weeks. Surviving cells were selected through each cell passage and were grown in the hypoxic condition up to 8 weeks. This strategy resulted in survival of only 5% of the cells. The surviving hypoxic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…On the other hand, there are clones within the tumor that react to hypoxic stress with adaptive processes that, through modification of gene expression, confer an aggressive phenotype, promoting local and distant spread (Fig. 4A, B) [8][9][10][11][12].…”
Section: Fallsmentioning
confidence: 99%
“…On the other hand, there are clones within the tumor that react to hypoxic stress with adaptive processes that, through modification of gene expression, confer an aggressive phenotype, promoting local and distant spread (Fig. 4A, B) [8][9][10][11][12].…”
Section: Fallsmentioning
confidence: 99%
“…5). For example, cells incubated under chronic hyp oxia for several weeks can have a higher invasive capacity than under acute hypoxia [2]. On the other hand, cells exposed to chronic hypoxia can be incapable of replication restart after reoxygenation and, therefore, should not contribute to continued tumorigenesis [61].…”
Section: Biological Consequencesmentioning
confidence: 99%
“…Correlation between SENP1 and HIF1␣ in Human Prostate Cancer-Elevated HIF1␣ levels are commonly observed in human PCa and are associated with more aggressive forms of the carcinoma (14,21,22). Because our previous studies suggested that SENP1 stabilizes HIF1␣ in mouse embryonic fibroblast cells and the studies above presented a similar phenomenon in adult mice, we sought to determine whether the level of SENP1 correlates with the elevated levels of HIF1␣ in human PCa.…”
Section: Senp1 Transgenic Mice Enhance Angiogenesis Via Stabilizationmentioning
confidence: 99%